Proprieties and Vagaries A Philosophical Thesis from Science, Horse Racing, Sexual Customs, Religion, and Politics - Hammond, Albert L (Johns Hopkins University Press, 2019)
Originally published in 1961. A constant influence on human action is that of proprieties, personal and social. These attitudes and traditions defining what is proper are largely logical in origin, but chance has a way of upsetting them. Even theory, which is part of human action, is subject to this influence. Dr. Hammond takes a novel approach to this philosophical theme. His topics of discussion include perception, the role of symbols in poetry and science, the definition of good and good use in language, space and the motion of the earth, the psychology of love, attitudes toward gambling, and a defense of horse racing. This unorthodox approach results in an exceptionally imaginative and thought-provoking book as well as a strong defense of deontology.